The era of artificial intelligence in malaysian higher education: impact and challenges in tangible mixed-reality learning system toward self exploration education (SEE) - Muhammad Fazil, Ahmad; Wan Rohila Ganti, Wan Abdul Ghapar (2019)
Artificial Intelligence (AI) is the creation of a smart machine that has human behaviour and response. AI in the education sector is able to interact, assist, and guide students through Self-Exploration Education (SEE) in Self Determined Learning (SDL) or Heutagogical technique, such as current, but semi-automatic learning systems. Malaysian higher education institutions are forced to adapt to such a radical change in order to stay competitive and fulfill their stakeholder needs. Everyone is born as a genius, with curiosity to explore the environment through experiments. This study examines the effect of SDL on SEE in Tangible Mixed-Reality Learning System until 2030. It does that under two different lenses: First, the effect on the value proposition and the business models of the SDL. Second, it identifies hurdles for the implementation and draws strategic implications for the SDL Tangible Mixed-Reality Learning System. However, in practice, SEE is still very much focused on spreading facts rather than encouraging personal exploration. Conducting exploration of learning in the classroom can be complicated for adult learning or andragogy and is limited by virtue, money and work infrastructure. But what if we can create a middle ground between learning and fiction, the world in which adults learn and explore in ways that may be impossible in real life but still true to the transfer of knowledge? The project is to craft an imaginative and accessible tool to help adults develop scientific minds and practices through self-exploration or Do-it-yourself DIY with a mixed reality learning system that empowers adults to know the invisible and investigate hard through exploration. By 2030 the likeliest scenario is that fully Self-Exploration is solely available for particularly high-value use cases, affecting the value proposition toward provision of education services, an increase of stakeholder and value-centric value propositions fostered by continuous interactions between the Heutagogical technique and the stakeholder.